Corruption and networks of interests in the Public Administration - Torres Pachas, David Ricardo (2019)
This article shows how corruption today manifests itself through networks of interests that infiltrate the Public Administration. These networks generate a system parallel to the formally recognized one that has its own actors and rules of the game. Proof of this are the recent cases involving high officials of the justice system and the construction company Odebrecht. To confront these forms of corruption, it will be necessary to understand the complexity of its diverse dynamics.